Uniform expansion of a polymeric helical stent - Paryab, Nasim (2013)
Helical coil polymeric stents provide an alternative method of stenting compared to traditional metallic stents, but require additional investigation to understand deployment, expansion, and fixation. A bilayer helical coil stent consisting of PLLA and PLGA was investigated using the finite element model to evaluate performance by uniform expansion and subsequent recoiling. In vitro material characterization studies showed that a preinsertion water-soaking step to mimic body implantation conditions provided the required ductility level expansion. In this case, the mechanical contribution of the outer PLGA layer was negligible since it softened significantly under environmental conditions. The viscoelastic response was not considered in this study since the strain rate during expansion was relatively slow and the material response was primarily plastic. The numerical model was validated with available experimental expansion and recoiling data. A parametric study was then undertaken to investigate the effect of stent geometry and coefficient of friction at the stent-cylinder interface on the expansion and recoiling characteristics. The model showed that helical stents exhibit a uniform stress distribution after expansion, which is important for controlled degradation when using biodegradable materials. The results indicated that increasing stent width, pitch value, and coil thickness resulted in a larger diameter after recoiling, which would improve fixation in the artery. It was also noted that a helical stent should have more than five coils to be stable after recoiling. This work is part of a larger research study focused on the performance of a balloon-inflated polymeric helical stent for artery applications.